Role of Short-Range Order and Hyperuniformity in the Formation of Band Gaps in Disordered Photonic Materials - Luis S., Froufe-Pérez; Engel, Michael; Damasceno, Pablo F.; Muller, Nicolas; Haberko, Jakub; Glotzer, Sharon C.; Scheffold, Frank (Physical Review Letters, 2016)
We study photonic band gap formation in two-dimensional high-refractive-index disordered materials where the dielectric structure is derived from packing disks in real and reciprocal space. Numerical calculations of the photonic density of states demonstrate the presence of a band gap for all polarizations in both cases. We find that the band gap width is controlled by the increase in positional correlation inducing short-range order and hyperuniformity concurrently. Our findings suggest that the optimization of short-range order, in particular the tailoring of Bragg scattering at the isotropic Brillouin zone, are of key importance for designing disordered PBG materials.